The Concept “Youth” in English and Tatar Linguistic Cultures - Motygullina, Zukhra A.; Nurgalieva, Leila A. (Journal of History Culture and Art Research, 2017)
The purpose of this article is to compare the concept of "youth" in two genetically unrelated languages – Tatar and English. The study implements methods of comparative, definitional, component and contextual analysis and ethnic-linguistic-culturological comparison. An exceptional importance of the concept of "youth" made it one of the key concepts of many peoples. In this paper, based on English and Tatar dictionaries, we presented the concept of "youth" in the form of a frame. We identified the distinctive and similar features of the concept of "youth" in English and Tatar. The materials of this article can be used in the practice of intercultural communication, in the translation process of teaching English to the Tatar audience at higher education institutions and schools in order to develop intercultural communication among learners.